Racial awareness in Phillis Wheatley's selected poems - Mani, Manimangai (SciPress, 2015)
Slavery in America began when Africans were brought in as slaves to the North American Colony of Jamestown Virginia around 1619. Slavery in America lasted for almost four hundred years though the trade was legally abolished by Britain in March 1807 (Walvin 163). Although the trade ended, slavery itself continued to survive. Phillis Wheatley (1753-1784) is considered the first prominent Black writer in the United States to publish a book of imaginative writing. She is also the first to start the African-American literary tradition, as well as the African American women literary tradition. Her work, which was derivative, was published in the collection, Poems on Various Subjects (1773) and in various magazines. Her choice of words was mostly biblical where it helped to camouflage her view on slavery. This paper intends to show that all of Wheatley’s poems actually carried the theme of freedom. She has intelligently used this theme to articulate her desires in a subtle manner. On the surface, the poems are all preaching the greatness of Christianity to the readers and urging them to find solace through religion. She shows her racial awareness and resistance through various themes of the poems that she wrote. This paper highlights Wheatley’s disapproval of slavery through her praise for religion, political commentaries, supporting elegies and death and finally through her escapism into an imaginary world.